(untitled) (Research, Society and Development, 2021)
Ecological, analytical and exploratory study that aimed to carry out epidemiological and spatial analyzes of the distribution of confirmed cases and deaths from Coronavirus 2019 disease (from English, Coronavirus Disease 2019 - COVID-19) that occurred in 2020, in the state of Piauí, Brazil. The variables listed were obtained via the IBGE and SESAPI database. In the epidemiological analyzes, descriptive statistics were performed and in the spatial analyzes, maps were constructed using geoprocessing techniques, through the statistical analyzes of Moran Global and Local. The results showed that, in 2020, 143,179 confirmed cases and 2,240 deaths caused by COVID-19 were reported in Piauí. There was a higher percentage of cases in females, young adults, and deaths in the elderly, males, with chronic diseases. Clusters were formed in the state, elements to be considered in the organization and strengthening of health services for the development of strategies that seek to minimize transmission during the emergence of COVID-19.